2012
DOI: 10.1002/cctc.201200245
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Carbonylation of Chloroacetates to Afford Malonates: Controlling the Selectivity of the Product in a Buffer

Abstract: We report an efficient process for the synthesis of diethyl malonate (DEM) and other malonates through the palladium‐catalyzed carbonylation of chloroacetates. Excellent selectivity (96 %) and yield (94 %) were obtained without the formation of Pd black. For the first time, a weakly alkaline buffer was used to control the selectivity for DEM in the reaction and we discuss the relationship between the buffer medium and selectivity in the reaction. The combination of anisole as the solvent and a Na2HPO4/NaH2PO4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…These results were also consistent with the observed experimental phenomena that the recovered catalyst kept a light brown colour during the recycling (Figure S3). The above results were different from the general immobilized palladium complexes, in which palladium species were usually partially reduced to palladium nanoparticles during the carbonylation reaction . Considering the structure of the catalyst, the good performance could be attributed to the high ligand concentration and excellent porous structure.…”
Section: Resultsmentioning
confidence: 66%
“…These results were also consistent with the observed experimental phenomena that the recovered catalyst kept a light brown colour during the recycling (Figure S3). The above results were different from the general immobilized palladium complexes, in which palladium species were usually partially reduced to palladium nanoparticles during the carbonylation reaction . Considering the structure of the catalyst, the good performance could be attributed to the high ligand concentration and excellent porous structure.…”
Section: Resultsmentioning
confidence: 66%
“…However, the presence of excess Me 4 NI afforded a little lower yield of diethyl malonate (entry 11). When the reaction time was further prolonged to 9 h, a high yield (94.9%) of diethyl malonate was obtained (entry 12), which was a little bit higher than that of a previously reported homogeneous and colloid catalyst [39,40]. Under the optimal conditions, we tried to lower the CO pressure, while a slight decrease in yield was observed (entry 13).…”
Section: Alkoxycarbonylation Reactionsmentioning
confidence: 85%
“…With the catalyst in hand, we started our investigation with the carbonylation of ethyl chloroacetate (ECA) as a model reaction. Previous results [39,40] showed that the solvent and base have great impacts on the activity and selectivity of this carbonylation reaction. Hence, the effect of solvent and base was first investigated.…”
Section: Alkoxycarbonylation Reactionsmentioning
confidence: 92%
See 2 more Smart Citations